2018
DOI: 10.1038/s41423-018-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of perforin/gasdermin/complement-formed pores in real cell membranes using atomic force microscopy

Abstract: Different types of pores ubiquitously form in cell membranes, leading to various types of cell death that profoundly influence the fate of inflammation and the disease status. However, these pores have never truly been visualized to date. Atomic force microscopy (AFM), which is emerging as a powerful tool to analyze the mechanical properties of biomolecules and cells, is actually an excellent imaging platform that allows biological samples to be visualized by probing surface roughness at the level of atomic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…Pyroptosis is a newly discovered form of programmed lytic cell death that is induced by inflammatory casapse-1 (CASP1), and is characterized by swelling of the cell, pore formation in unilamellar liposomes, membrane rupture and the release of inflammatory cytokines [14][15][16][17][18]. Gasdermin D (GSDMD) was discovered to be a substrate of CASP1, and cleavage of the N-terminal fragment of GSDMD forms membrane pores and drives pyroptosis [19][20][21]. Inflammasome complexes function as crucial intracellular effectors to initiate innate immunity and thus to defend against infections or tissue damage [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis is a newly discovered form of programmed lytic cell death that is induced by inflammatory casapse-1 (CASP1), and is characterized by swelling of the cell, pore formation in unilamellar liposomes, membrane rupture and the release of inflammatory cytokines [14][15][16][17][18]. Gasdermin D (GSDMD) was discovered to be a substrate of CASP1, and cleavage of the N-terminal fragment of GSDMD forms membrane pores and drives pyroptosis [19][20][21]. Inflammasome complexes function as crucial intracellular effectors to initiate innate immunity and thus to defend against infections or tissue damage [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution atomic force microscopy studies with GSDMD-N showed that monomers can first associate forming arcs or slit structures that later evolve into transmembrane pores with a ring shape. Notably, all these structures are able to perforate the membranes forming holes in the 10-30 nm range [28]. The fact that incomplete rings of GSDMD-N promote the opening of the membrane clearly indicates the direct involvement of lipids in pore opening.…”
Section: Pore Formation By Gsdms In Pyroptosismentioning
confidence: 96%
“…The lipid membrane provides a suitable environment to trigger the conformational changes required for their structural evolution from soluble monomers to membrane-embedded oligomers [27]. In recent years, our understanding of the mechanism of GSDMs pore formation has dramatically increased with the structural characterization of different variants in solution [10] and in membranes [27,28]. The analysis of the crystal structure of full-length GSDMA3 [10] and the cryo-electron microscopy structure of a GSDMA3-N pore isolated from reconstituted liposomes [27] shed light on the mechanisms of membrane insertion and pore assembly.…”
Section: Pore Formation By Gsdms In Pyroptosismentioning
confidence: 99%
“…Author Manuscript Published OnlineFirst on November 9, 2020; DOI: 10.1158/0008-5472. CAN-20-2569 The AFM tips (NPG-10) were functionalized with anti-PFR or anti-SLO antibody as described before (21). In brief, NPG-10 tips were coated with the crosslinker of NHS-PEG-maleimide for 1h at room temperature.…”
Section: Downloaded Frommentioning
confidence: 99%